Endothelial intercellular cell adhesion molecule 1 contributes to cell aggregate formation in CHO cells cultured in serum‐free media. (2nd January 2020) - Louie, Salina; Heidersbach, Amy; Blanco, Noelia; Haley, Benjamin; Rose, Christopher M.; Liu, Peter S.; Yim, Mandy; Tang, Danming; Lam, Cynthia; Sandoval, Wendy N.; Shaw, David; Snedecor, Brad; et al.
Abstract: Chinese hamster ovary (CHO) cells have been adapted to grow in serum‐free media and in suspension culture to facilitate manufacturing needs. Some CHO cell lines, however, tend to form cell aggregates while being cultured in suspension. This can result in reduced viability and capacity for single cell cloning (SCC) via limiting dilution, and process steps to mitigate cell aggregate formation, for example, addition of anti‐cell‐aggregation agents. In this study, we have identified endothelial intercellular cell adhesion molecule 1 (ICAM‐1) as a key protein promoting cell aggregate formation in a production competent CHO cell line, which is prone to cell aggregate formation. Knocking out (KO) the ICAM‐1 gene significantly decreased cell aggregate formation in the culture media without anti‐cell‐aggregation reagent. This trait can simplify the process of transfection, selection, automated clone isolation, and so on. Evaluation in standard cell line development of ICAM‐1 KO and wild‐type CHO hosts did not reveal any noticeable impacts on titer or product quality. Furthermore, analysis of a derived nonaggregating cell line showed significant reductions in expression of cell adhesion proteins. Overall, our data suggest that deletion of ICAM‐1 and perhaps other cell adhesion proteins can reduce cell aggregate formation and improve clonality assurance during SCC.